Effects of Smoke on Surface Observations, Turbulence, and Proposed Subcritical Aerosol-Moisture Feedback (SAMF) During the 8 April 2024 Solar Eclipse in Columbus, GA, USA - Stephen M. Jessup; Britney Blaire Enfinger (Atmosphere)
Very rarely, the atmosphere produces a natural experiment that, if captured, has the potential to lend insight into the fundamentals of atmospheric behavior. During the North American solar eclipse on 8 April 2024, a prescribed fire on the grounds of Fort Benning produced a smoky haze in Columbus, Georgia, USA. This haze covered the Columbus State University main campus and the nearby Columbus Airport (KCSG) leading up to and during the peak of the eclipse. Automated Surface Observing Station (ASOS) and Georgia Weather Network observations were examined for the event. At the time of temperature minimum, the temperature depression at KCSG was 0.5 °C greater than at nearby ASOS stations. An “eclipse wind” was observed at KCSG but not at the nearby ASOS stations. Based on observations of steady-state air and dewpoint temperatures, together with rapid fluctuations in visibility, we propose the Subcritical Aerosol-Moisture Feedback (SAMF) mechanism, in which subtle feedbacks among particle growth, relative humidity, and scattering of radiation by aerosol-laden air may maintain steady-state thermodynamic conditions. This case study offers a unique opportunity to examine aerosol behavior under transient radiative forcing, suggesting insights into how a smoky environment enhances thermal buffering and stabilizes the boundary-layer response under rare conditions.